2011
DOI: 10.1093/geronb/gbr092
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Midlife Educational, Work, Health, and Family Experiences on Men's Early Retirement

Abstract: Given the destandardization of life courses, information on distal life experiences might become even more important toward understanding retirement in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 27 publications
3
80
0
3
Order By: Relevance
“…Similarly, by analyzing more recent data of the SHARELIFE 3 survey, Kovalenko and Mortelmans (2013) have shown that individuals following a so-called 'stepping stone' career trajectory -characterized by a main job of a prolonged duration that is held until retirementretire earlier than those individuals who had a 'hypertransitional' career trajectory. Other studies suggest as well that mobility is associated with later retirement among men, by showing that mid-life employer changes are associated with weaker intentions to retire early (Damman et al 2011), and that a shorter job tenure decreases retirement risks (Hayward et al 1998).…”
Section: Work Histories and Retirement Timingmentioning
confidence: 97%
See 4 more Smart Citations
“…Similarly, by analyzing more recent data of the SHARELIFE 3 survey, Kovalenko and Mortelmans (2013) have shown that individuals following a so-called 'stepping stone' career trajectory -characterized by a main job of a prolonged duration that is held until retirementretire earlier than those individuals who had a 'hypertransitional' career trajectory. Other studies suggest as well that mobility is associated with later retirement among men, by showing that mid-life employer changes are associated with weaker intentions to retire early (Damman et al 2011), and that a shorter job tenure decreases retirement risks (Hayward et al 1998).…”
Section: Work Histories and Retirement Timingmentioning
confidence: 97%
“…In studies on life histories and retirement, the financial argument is the most central argument that has been used to theoretically link earlier experiences to later outcomes: Earlier life experiences will affect preretirement financial opportunities and constraints and consequently retirement decisions (e.g., Hank 2004, Hayward et al 1998, Szinovacz and DeViney 2000, Damman et al 2011). …”
Section: Linking Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations